Rice Na+-Permeable Transporter OsHAK12 Mediates Shoots Na+ Exclusion in Response to Salt Stress - Zhang, Linan; Sun, Xiangyu; Li, Yanfang; Luo, Xuan; Song, Shaowen; Chen, Yan; Wang, Xiaohui; Mao, Dandan; Chen, Liangbi; Luan, Sheng (Frontiers in Plant Science, 2021)
Soil salinity has become a major stress factor that reduces crop productivity worldwide. Sodium (Na+) toxicity in a number of crop plants is tightly linked with shoot Na+ overaccumulation, thus Na+ exclusion from shoot is crucial for salt tolerance in crops. In this study, we identified a member of the high-affinity K+ transporter (HAK), OsHAK12, which mediates shoots Na+ exclusion in response to salt stress in rice. The Oshak12 mutants showed sensitivity to salt toxicity and accumulated more Na+ in the xylem sap, leading to excessive Na+ in the shoots and less Na+ in the roots. Unlike typical HAK family transporters that transport K+, OsHAK12 is a Na+-permeable plasma membrane transporter. In addition, OsHAK12 was strongly expressed in the root vascular tissues and induced by salt stress. These findings indicate that OsHAK12 mediates Na+ exclusion from shoot, possibly by retrieving Na+ from xylem vessel thereby reducing Na+ content in the shoots. These findings provide a unique function of a rice HAK family member and provide a potential target gene for improving salt tolerance of rice.